2022
DOI: 10.1172/jci156243
|View full text |Cite
|
Sign up to set email alerts
|

α Cell dysfunction in islets from nondiabetic, glutamic acid decarboxylase autoantibody–positive individuals

Abstract: BACKGROUND Multiple islet autoantibodies (AAbs) predict the development of type 1 diabetes (T1D) and hyperglycemia within 10 years. By contrast, T1D develops in only approximately 15% of individuals who are positive for single AAbs (generally against glutamic acid decarboxylase [GADA]); hence, the single GADA + state may represent an early stage of T1D. METHODS Here, we functionally, histologically, and molecularly phenotyped human islets from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 61 publications
1
27
1
Order By: Relevance
“…That GABA reinforces the inhibitory communication from beta to alpha cells suggests the islet GABA system as a target to treat diabetes. Dysregulation of alpha cell glucagon secretion in low glucose contributes to diabetic hyperglycemia and is observed in T2D, T1D and pre-T1D autoantibody positive individuals ( 136 , 137 ). Coincidentally, islets from donors with T2D and T1D are also observed to be depleted of GABA ( 12 ).…”
Section: Effect Of Gaba On Glucagon Secretionmentioning
confidence: 99%
“…That GABA reinforces the inhibitory communication from beta to alpha cells suggests the islet GABA system as a target to treat diabetes. Dysregulation of alpha cell glucagon secretion in low glucose contributes to diabetic hyperglycemia and is observed in T2D, T1D and pre-T1D autoantibody positive individuals ( 136 , 137 ). Coincidentally, islets from donors with T2D and T1D are also observed to be depleted of GABA ( 12 ).…”
Section: Effect Of Gaba On Glucagon Secretionmentioning
confidence: 99%
“…For example, impaired glucagon secretion among diabetic patients has been identified for decades [34,35]. This result is supported by recent experiments performed on islets isolated from diabetic patients showing both a decreased expression of key alpha cellsenriched transcription factors, and a loss of glucose-regulated glucagon secretion [36,37]. A limited number of studies also suggest an alteration of delta cells function in type 1 diabetes [38,39].…”
Section: Introductionmentioning
confidence: 80%
“…The observation implies that those children who later present with type 1 diabetes may have variable glucose metabolism in their early years. Although reasons behind this remain speculative, previous studies have shown alterations also in glucagon-producing alpha cells in preclinical type 1 diabetes ( 25 ). It remains possible that alpha cell dysfunction is presently lost prior to decreasing insulin secretion leading to hypoglycemia in future progressors.…”
Section: Discussionmentioning
confidence: 99%